Robot-assisted and fluoroscopy-guided pedicle screw placement: a systematic review - Marcus,HJ; Cundy,TP; Nandi,D; Yang,G-Z; Darzi,A (European Spine Journal, 2014)
PurposeAt present, most spinal surgeons undertake pedicle screw implantation using either anatomical landmarks or C-arm fluoroscopy. Reported rates of screw malposition using these techniques vary considerably, though the evidence generally favors the use of image-guidance systems. A miniature spine-mounted robot has recently been developed to further improve the accuracy of pedicle screw placement. In this systematic review, we critically appraise the perceived benefits of robot-assisted pedicle screw placement compared to conventional fluoroscopy-guided technique.MethodsThe Cochrane Central Register of Controlled Trials, PubMed, and EMBASE databases were searched between January 2006 and January 2013 to identify relevant publications that (1) featured placement of pedicle screws, (2) compared robot-assisted and fluoroscopy-guided surgery, (3) assessed outcome in terms of pedicle screw position, and (4) present sufficient data in each arm to enable meaningful comparison (>10 pedicle screws in each study group).ResultsA total of 246 articles were retrieved, of which 5 articles met inclusion criteria, collectively reporting placement of 1,308 pedicle screws (729 robot-assisted, 579 fluoroscopy-guided). The findings of these studies are mixed, with limited higher level of evidence data favoring fluoroscopy-guided procedures, and remaining comparative studies supporting robot-assisted pedicle screw placement.ConclusionsThere is insufficient evidence to unequivocally recommend one surgical technique over the other. Given the high cost of robotic systems, and the high risk of spinal surgery, further high quality studies are required to address unresolved clinical equipoise in this field.